The Curtin Materials Availability Survey 2017 - Wells, David (2018)
This paper extends the principles of earlier print-based availability surveys to the context of today's electronic library, and explores the question of an appropriate methodology. The ability of clients to find what they want remains a central question, as does the library's ability to identify and address the reasons that clients fail to find what they are looking for.